The structure of a pentachromium(ii) extended metal atom chain at 3 K: Cotton's conjecture proven. Issue 44 (7th November 2022) - Cornia, Andrea; Nicolini, Alessio; McMonagle, Charles J.; Probert, Michael R.
Abstract : Cryocrystallography down to 3 K and twin refinement disclose the actual solid-state symmetry of [Cr5 (C15 H11 N5 )4 (NCS)2 ], an archetypal EMAC. As conjectured by F. A. Cotton, the molecule is unsymmetric, with alternating long/short Cr–Cr separations. Abstract : We provide definitive experimental proof that the archetypal string-like compound [Cr5 (tpda)4 (NCS)2 ] has alternating long and short Cr–Cr separations in the solid state, as conjectured by F. A. Cotton, rather than essentially equally spaced Cr atoms, as initially claimed (H2 tpda = N 2, N 6 -di(pyridin-2-yl)pyridine-2, 6-diamine). Single-crystal X-ray data collected from 292 to 3 K revealed that the misinterpretation is caused by pseudo-merohedral twinning and that bond length alternation is enhanced at low temperature.